Do emergency cervical cerclages make a difference? A 10-year retrospective study. (16th November 2010) - Varghese, S; Myers, J; Juverdeanu, S; Kamran, M; Gillham, JC
Abstract : Background: 'Emergency' or 'rescue' cervical cerclage is used in women with threatened midtrimester spontaneous abortion and preterm labour. A recent meta-analysis concluded there was no conclusive evidence of benefit in the insertion of a cervical stitch in these women until more data become available. Aim: To assess the outcome of pregnancies when an emergency cerclage was performed. Methods: Retrospective review of patients who underwent emergency cervical cerclage from 1998 to 2009 in a tertiary centre with 5500 deliveries p.a. Patients presenting with symptoms of preterm labour/threatened spontaneous abortion. Asymptomatic women with shortened cervix on scan were excluded. Results: A total of 105 emergency sutures were inserted between 1998 and 2009. The median gestational age at insertion was 23 completed weeks (range 16–28) and the median days gained was eight (range 0–113). There was no significant correlation between gestation at insertion and days gained (Spearman 0.09, p>0.05). Of the women who had a suture inserted at <23 completed weeks (n=53), 21 (40%) delivered after 23 completed weeks, of which eight (15%) delivered after 26 completed weeks. For women with a suture inserted before 21 completed weeks (n=30), five delivered after 23 weeks and three delivered after 26 weeks. There was no significant difference between primips (n=49) and multips (n=46) (median days gained eight, range 1–74 vs eight, 0–113). Conclusion: These data suggest that emergency cervical cerclage is of limited efficacy particularly when inserted before 23 weeks. Accurate counselling with realistic prognosis is essential for women who present with threatened preterm labour prior to emergency cerclage.